A Timed Off-Switch for Dynamic Control of Gene Expression in Corynebacterium Glutamicum - Siebert, Daniel; Altenbuchner, Josef; Blombach, Bastian (Frontiers in Bioengineering and Biotechnology, 2021)
Dynamic control of gene expression mainly relies on inducible systems, which require supplementation of (costly) inducer molecules. In contrast, synthetic regulatory circuits, which allow the timed shutdown of gene expression, are rarely available and therefore represent highly attractive tools for metabolic engineering. To achieve this, we utilized the VanR/PvanABK* regulatory system of Corynebacterium glutamicum, which consists of the transcriptional repressor VanR and a modified promoter of the vanABK operon (PvanABK*). VanR activity is modulated by one of the phenolic compounds ferulic acid, vanillin or vanillic acid, which are co-metabolized with D-glucose. Thus, gene expression in the presence of D-glucose is turned off if one of the effector molecules is depleted from the medium. To dynamically control the expression of the aceE gene, encoding the E1 subunit of the pyruvate dehydrogenase complex which is essential for growth on D-glucose, we replaced the native promoter by vanR/PvanABK* yielding C. glutamicum ΔPaceE::vanR-PvanABK*. The biomass yield of this strain increased linearly with the supplemented amount of effector. After consumption of the phenolic compounds growth ceased, however, C. glutamicum ΔPaceE::vanR-PvanABK* continued to utilize the residual D-glucose to produce significant amounts of pyruvate, L-alanine and L-valine. Interestingly, equimolar concentrations of the three phenolic compounds resulted in different biomass yields and with increasing effector concentration, the product spectrum shifted from pyruvate over L-alanine to L-valine. To further test the suitability of the VanR/PvanABK* system, we overexpressed the L-valine biosynthesis genes ilvBNCE in C. glutamicum ΔPaceE::vanR-PvanABK* which resulted in efficient L-valine production with a yield of about 0.36 mol L-valine per mol D-glucose. These results demonstrate that the VanR/PvanABK* system is a valuable tool to control gene expression in C. glutamicum in a timed manner by one of the cheap and abundant phenolic compounds ferulic acid, vanillin and vanillic acid.